Isolation of Double Negative αβ T Cells from the Kidney - Martina, Maria N. (MyJove Corporation, 2014)
There is currently no standard protocol for the isolation of DN T cells from the non-lymphoid tissues despite their increasingly reported involvement in various immune responses. DN T cells are a unique immune cell type that has been implicated in regulating immune and autoimmune responses and tolerance to allotransplants(1-6). DN T cells are, however, rare in peripheral blood and secondary lymphoid organs (spleen and lymph nodes), but are major residents of the normal kidney. Very little is known about their pathophysiologic function(7) due to their paucity in the periphery. We recently described a comprehensive phenotypic and functional analysis of this population in the kidney(8) in steady state and during ischemia reperfusion injury. Analysis of DN T cell function will be greatly enhanced by developing a protocol for their isolation from the kidney. Here, we describe a novel protocol that allows isolation of highly pure ab CD4+ CD8+ T cells and DN T cells from the murine kidney. Briefly, we digest kidney tissue using collagenase and isolate kidney mononuclear cells (KMNC) by density gradient. This is followed by two steps to enrich hematopoietic T cells from 3% to 70% from KMNC. The first step consists of a positive selection of hematopoietic cells using a CD45+ isolation kit. In the second step, DN T cells are negatively isolated by removal of non-desired cells using CD4, CD8, and MHC class II monoclonal antibodies and CD1d α-galcer tetramer. This strategy leads to a population of more than 90% pure DN T cells. Surface staining with the above mentioned antibodies followed by FACs analysis is used to confirm purity.